Calculus and analytic geometry - Thomas, George B. (New York Addison Wesley, 1968)
This book presents a modern view of calculus enhanced by technology. It contains exercises and problem-solving strategies to help the student better grasp the different techniques offered..
Includes index
Keywords: Quản trị kinh doanh